Composite positive electrode active material, battery cell, battery, and power using device
Patent Information
- Application Number
- CN202310300449.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-24
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-03-24
AI Technical Summary
但是,相关技术中电池单体在使用过程中,正极活性材料的电压降过大,不利于电池单体能量密度的提升
Smart Images

Figure CN118693246B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of batteries, specifically to a composite positive electrode active material, a battery cell, a battery, and an electrical device. Background Technology
[0002] Battery cells have characteristics such as high capacity and long lifespan, and are therefore widely used in electronic devices such as mobile phones, laptops, electric vehicles, electric cars, electric airplanes, electric ships, electric toy cars, electric toy ships, electric toy airplanes, and power tools, etc.
[0003] As battery applications become increasingly widespread, the requirements for battery performance are becoming more stringent. However, in related technologies, excessive voltage drop in the positive electrode active material during battery cell use is detrimental to improving the energy density of the battery cell. Summary of the Invention
[0004] This application is made in view of the above-mentioned issues, and its purpose is to provide a composite positive electrode active material, a battery cell, a battery, and an electrical device.
[0005] The first aspect of this application provides a composite positive electrode active material, which includes a first lithium manganese iron phosphate material and a second lithium manganese iron phosphate material. The first lithium manganese iron phosphate material has a nanosheet structure, and the (010) crystal surface area of the first lithium manganese iron phosphate material accounts for A1% of the total crystal surface area of the first lithium manganese iron phosphate material. The second lithium manganese iron phosphate material has a spherical and / or near-spherical structure, and the (010) crystal surface area of the second lithium manganese iron phosphate material accounts for A2% of the total crystal surface area of the second lithium manganese iron phosphate material. The composite positive electrode active material satisfies: A1 > A2.
[0006] Therefore, the nanosheet structure of the first lithium manganese iron phosphate material in the embodiments of this application results in a larger area of the (010) crystal plane of the first lithium manganese iron phosphate material, and its capacity is close to the theoretical capacity. After the first lithium manganese iron phosphate material and the second lithium manganese iron phosphate material are mixed to form a composite positive electrode active material, the overall capacity of the composite positive electrode active material is improved and the average discharge voltage is improved. As a result, when the composite positive electrode active material is applied to a battery cell, the energy density of the battery cell is significantly improved.
[0007] In some embodiments, the cell parameter b-axis length of the first lithium manganese iron phosphate material is b1, and its unit is nm; the cell parameter b-axis length of the second lithium manganese iron phosphate material is b2, and its unit is nm, wherein b1 < b2.
[0008] Therefore, the cell parameter b-axis of the first lithium manganese iron phosphate material in the embodiments of this application is relatively short, which can further shorten the lithium ion diffusion distance, which is conducive to realizing the rapid transport of lithium ions and improving the rate performance of the battery cell.
[0009] In some implementations, b1 < 100; further alternatively, 10 ≤ b1 ≤ 80.
[0010] In some implementations, b2 > 100; further alternatively, 200 ≤ b2 ≤ 800.
[0011] In some embodiments, the average voltage of the composite positive electrode active material is 3.55V to 3.81V.
[0012] In some embodiments, the composite positive electrode active material has a first discharge voltage plateau U1 and a second discharge voltage plateau U2, where 4.0V≤U1<4.1V; and / or 3.4V≤U2≤3.6V.
[0013] Therefore, the second lithium manganese iron phosphate material in the embodiments of this application has two voltage platforms, a manganese platform of 4.1V and an iron platform of 3.5V, due to the incorporation of manganese. Compared with materials such as lithium iron phosphate, it has a relatively high voltage platform. Due to the mixed use of the first lithium manganese iron phosphate material and the second lithium manganese iron phosphate material, the composite positive electrode active material has a significant voltage boost, which can significantly improve the energy density of the composite positive electrode active material.
[0014] In some embodiments, the resistivity of the composite positive electrode active material powder is from 1 Ω·cm to 500 Ω·cm.
[0015] In some embodiments, the powder compaction density of the composite positive electrode active material is from 2.19 g / ml to 2.40 g / ml.
[0016] In some embodiments, the X-ray diffraction pattern of the first lithium manganese iron phosphate material has characteristic peaks I(020) and I(200), and I(020) / I(200) > 2.1.
[0017] In some embodiments, the X-ray diffraction (XRD) pattern of the second lithium manganese iron phosphate material has characteristic peaks I(020) and I(200), and I(020) / I(200) ≤ 2.1.
[0018] In some embodiments, the thickness of the first lithium manganese iron phosphate material is H, with units of nm, and 10 ≤ H ≤ 80. When the thickness of the first lithium manganese iron phosphate material is within the above range, it is beneficial for the first lithium manganese iron phosphate material to be distributed between the particles of the second lithium manganese iron phosphate material, forming a conductive network structure. This can improve the intrinsic resistance of the composite positive electrode active material and increase the powder conductivity.
[0019] In some embodiments, based on the total mass of the composite cathode active material, the mass percentage of the first lithium manganese iron phosphate material is B1%, the mass percentage of the second lithium manganese iron phosphate material is B2%, and 1 ≤ B2 / B1 ≤ 19. When the mass percentages of the first and second lithium manganese iron phosphate materials meet the above ranges, the discharge voltage plateau of the composite cathode active material can be significantly improved, thereby increasing the energy density of the battery cell.
[0020] In some embodiments, the volume average particle size of the first lithium manganese iron phosphate material is D. v50-1 Its unit is nm; the volume average particle size of lithium manganese iron phosphate materials is D. v50-2 Its unit is nm, where 1 ≤ D v50-2 / D v50-1 ≤16; optionally, 2≤D v50-2 / D v50-1 ≤16;
[0021] Therefore, the present invention obtains a composite material by mixing two types of lithium manganese iron phosphate particles with different particle sizes. By improving the packing density between particles through the gradation relationship between particles, the composite material can have a relatively high compaction density and improve the energy density of the battery cell.
[0022] In some implementations, 50≤D v50-1 ≤300; and / or 200≤D v50-2 ≤800.
[0023] In some embodiments, the specific surface area of the first lithium manganese iron phosphate material is S1, and its unit is m². 2 / g; The specific surface area of lithium iron phosphate second-phosphate materials is S2, and its unit is m. 2 / g; where 0.4≤S2 / S1<1.0.
[0024] Therefore, when the specific surface area of the first lithium manganese iron phosphate material and the specific surface area of the second lithium manganese iron phosphate material in the embodiments of this application are within the above range, it is more conducive to the formation of a connected conductive network structure by the first lithium manganese iron phosphate material, thereby improving the electronic powder conductivity and electronic powder conductivity of the composite positive electrode active material.
[0025] In some implementations, 20 ≤ S1 ≤ 50; and / or 8 ≤ S2 ≤ 20.
[0026] In some embodiments, the first lithium manganese iron phosphate material and the second lithium manganese iron phosphate material each independently comprise a material with the molecular formula LiFe. (1-x) Mn x Compounds of PO4 and their modified compounds, wherein 0.5 ≤ x < 1.
[0027] A second aspect of this application also provides a battery cell including a positive electrode sheet, said positive electrode sheet comprising a composite positive electrode active material as described in any embodiment of the first aspect of this application.
[0028] A third aspect of this application also provides a battery comprising a battery cell as described in any embodiment of the second aspect of this application.
[0029] The fourth aspect of this application also provides an electrical device, including a battery as described in any embodiment of the third aspect of this application. Attached Figure Description
[0030] To more clearly illustrate the technical solutions of the embodiments of this application, the drawings used in the embodiments of this application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort.
[0031] Figure 1 This is a schematic diagram of one embodiment of the battery cell of this application.
[0032] Figure 2 yes Figure 1 An exploded view of the implementation method of the battery cell.
[0033] Figure 3 This is a schematic diagram of one embodiment of the battery module of this application.
[0034] Figure 4 This is a schematic diagram of one embodiment of the battery pack of this application.
[0035] Figure 5 yes Figure 4 An exploded view of an embodiment of the battery pack shown.
[0036] Figure 6 This is a schematic diagram of one embodiment of an electrical device that uses the battery cell of this application as a power source.
[0037] Figure 7 a is a scanning electron microscope (SEM) image of the first lithium manganese iron phosphate composite positive electrode active material in Example 1.
[0038] Figure 7 b is a scanning electron microscope (SEM) image of the second manganese iron lithium phosphate material of the composite positive electrode active material in Example 1.
[0039] Figure 8 This is a transmission electron microscope (TEM) image of the composite positive electrode active material of Example 1.
[0040] Figure 9 This is a scanning electron microscope (SEM) image of the composite positive electrode active material of Example 1.
[0041] Figure 10 These are charge-discharge curves of the composite positive electrode active materials of Example 1 and Comparative Example 1.
[0042] The accompanying drawings may not be drawn to scale.
[0043] The annotations in the attached figures are explained as follows:
[0044] 1. Battery pack; 2. Upper casing; 3. Lower casing; 4. Battery module;
[0045] 5. Battery cell; 51. Housing; 52. Electrode assembly;
[0046] 53. Cover plate;
[0047] 6. Electrical appliances. Detailed Implementation
[0048] The following detailed description discloses embodiments of the composite positive electrode active material, battery cell, battery, and power device of this application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of actually identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.
[0049] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0050] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions. Unless otherwise specified, all technical features and optional technical features of this application can be combined to form new technical solutions.
[0051] Unless otherwise specified, all steps of this application may be performed sequentially or randomly, preferably sequentially. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, if the method may also include step (c), it means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0052] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0053] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0054] In this application, the terms "multiple" or "various" refer to two or more kinds.
[0055] Polyanionic compounds are a series of compounds containing tetrahedral or octahedral anionic structural units. These compounds have stable crystal framework structures and can maintain stable structures even when a large number of lithium ions are inserted or extracted. For example, when lithium ions are inserted or extracted in cathode materials, the structural rearrangement of the material is very small. In addition, the discharge potential plateau of the material can be modulated by configuring different chemical elements.
[0056] Polyanionic compounds include lithium iron phosphate, lithium manganese phosphate, and lithium manganese iron phosphate, among others. Lithium manganese iron phosphate combines the excellent properties of both lithium iron phosphate and lithium manganese phosphate, exhibiting stable chemical properties and high safety. Its crystal structure is orthorhombic olivine, resulting in good thermal stability and low oxidizability. To improve material performance, related technologies have employed methods such as blending materials with different particle sizes, and even combining polyanionic compounds with ternary materials. However, while these methods can leverage the strengths of both and improve the physical parameters of the materials, they offer minimal improvement to their electrochemical and intrinsic characteristics. Furthermore, the voltage drop of lithium manganese iron phosphate remains excessive, leading to relatively low energy density in battery cells when applied to them.
[0057] In view of the above problems, this application proposes a composite positive electrode active material, which includes two types of mixed lithium manganese iron phosphate materials, especially one of the lithium manganese iron phosphate materials is a material with (010) crystal facet exposed. The capacity of this type of material is close to the theoretical capacity, which can significantly improve the average discharge voltage of lithium manganese iron phosphate, thereby improving the energy density of the battery cell.
[0058] Composite positive electrode active materials
[0059] In a first aspect, this application proposes a composite positive electrode active material, which includes a first lithium manganese iron phosphate material and a second lithium manganese iron phosphate material; the first lithium manganese iron phosphate material has a nanosheet structure, and the (010) crystal surface area of the first lithium manganese iron phosphate material accounts for A1% of the total crystal surface area of the first lithium manganese iron phosphate material; the second lithium manganese iron phosphate material has a spherical and / or near-spherical structure, and the (010) crystal surface area of the second lithium manganese iron phosphate material accounts for A2% of the total crystal surface area of the second lithium manganese iron phosphate material; the composite positive electrode active material satisfies: A1>A2.
[0060] The second type of lithium manganese iron phosphate material is a spherical and / or near-spherical material. This type of material can be a secondary particle composed of primary particle agglomeration, or it can be a primary particle, or a mixture of primary and secondary particles.
[0061] The first type of lithium manganese iron phosphate material has a nanosheet structure, which can be understood as a material whose thickness is much smaller than its length or width. It can be one or more of the following: triangular sheet, square sheet, and hexagonal sheet. Due to the nanosheet structure of the first type of lithium manganese iron phosphate material, the area of the (010) crystal plane of the first type of lithium manganese iron phosphate material is relatively large, and its capacity is close to the theoretical capacity. After the first type of lithium manganese iron phosphate material and the second type of lithium manganese iron phosphate material are mixed to form a composite positive electrode active material, the overall capacity of the composite positive electrode active material is improved, and the average discharge voltage is improved. As a result, when the composite positive electrode active material is applied to a battery cell, the energy density of the battery cell is significantly improved.
[0062] In some embodiments, 40 ≤ A1 ≤ 80. Optionally, 40 ≤ A1 ≤ 74. Exemplarily, the ratio of the (010) crystal plane area of the first lithium manganese iron phosphate material to the total crystal plane area of the first lithium manganese iron phosphate material can be 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58%, 60%, 65%, 70%, 74%, 75%, 80%, or a range of any two of the above values.
[0063] In some embodiments, 20 ≤ A2 ≤ 40. Optionally, 31 ≤ A2 ≤ 38. The ratio of the (010) crystal plane area of the second lithium manganese iron phosphate material to the total crystal plane area of the second lithium manganese iron phosphate material can be 20%, 22%, 25%, 28%, 30%, 31%, 32%, 35%, 38%, 40%, or any combination of two of the above values.
[0064] During spontaneous growth, crystals can develop into polyhedral shapes composed of planes with different orientations. The planes in the polyhedral shape are called crystal faces. A crystal face is a plane formed by any three lattice points that are not on the same straight line in the crystal structure, representing the orientation of the atomic planes in the crystal. A coordinate system (crystal axis system) is defined in the crystal. The crystal axis system has three crystal axes intersecting at the center of the crystal, namely the a-axis, b-axis, and c-axis. Exposed crystal faces refer to the crystal faces formed by the atoms on the surface of the material, which can also be considered as crystal faces in contact with the external environment. In this application, the largest surface of the particle is used as the observation point. The lattice spacing is measured with high resolution by transmission electron microscopy (TEM). The (200) and (002) crystal faces can be determined based on the lattice spacing. After the two crystal faces are confirmed, the one perpendicular to these two crystal faces is the (010) crystal face.
[0065] Of course, the embodiments of this application can also use an X-ray powder diffractometer to determine the crystal structure of the composite positive electrode active material. For example, a Brucker D8A_A25 X-ray diffractometer from Brucker AxS in Germany can be used with CuKα rays as the radiation source, the ray wavelength scanning 2θ angle range is 10° to 90°, and the scanning rate is 4° / min.
[0066] During the charging and discharging process of a single battery cell, lithium ions are transported one-dimensionally along the (010) crystal plane, i.e., the b-axis direction. Charge transfer mainly occurs on the (010) crystal plane. The main exposed crystal plane of the first lithium manganese iron phosphate material in this application is the (010) crystal plane. The first lithium manganese iron phosphate material, when used in conjunction with the second lithium manganese iron phosphate material, can reduce the internal resistance of the composite positive electrode active material, improve the ionic powder conductivity and electronic powder conductivity of the composite positive electrode active material, reduce the intrinsic resistance, and improve the low-temperature performance and rate performance of the battery cell.
[0067] In some embodiments, the b-axis length of the cell parameter of the first lithium manganese iron phosphate material is b1, with units of nm; the b-axis length of the cell parameter of the second lithium manganese iron phosphate material is b2, with units of nm, wherein b1 < b2. The relatively shorter b-axis of the cell parameter of the first lithium manganese iron phosphate material can further shorten the lithium-ion diffusion distance, which is beneficial to achieving rapid lithium-ion transport and improving the rate performance of the battery cell.
[0068] In some implementations, b1 < 100. Optionally, 10 ≤ b1 ≤ 80. For example, the b-axis length of the cell parameter of the first lithium manganese iron phosphate material can be 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 85 nm, or any range of two of the above values.
[0069] In some implementations, b2 > 100. Optionally, 200 ≤ b2 ≤ 800. For example, the b-axis length of the cell parameter of the second lithium manganese iron phosphate material can be 110 nm, 120 nm, 150 nm, 180 nm, 200 nm, 250 nm, 300 nm, 400 nm, 450 nm, 500 nm, 600 nm, 700 nm, 800 nm, 850 nm, or a range of any two of the above values.
[0070] In some embodiments, the average voltage of the composite positive electrode active material is 3.55V to 3.81V, which significantly improves the average voltage of the composite positive electrode active material. For example, the average voltage of the composite positive electrode active material can be 3.55V, 3.60V, 3.65V, 3.70V, 3.75V, 3.80V, 3.81V, or a range of any two of the above values.
[0071] In the embodiments of this application, the average voltage of the composite positive electrode active material is the ratio of the discharge energy density to the specific capacity of the battery cell using the composite positive electrode active material, for example, the above value is obtained by charging and discharging at a rate of 0.1C.
[0072] In some embodiments, the composite positive electrode active material has a first discharge voltage plateau U1 and a second discharge voltage plateau U2, where 4.0V ≤ U1 < 4.1V; and / or 3.4V ≤ U2 ≤ 3.6V. Exemplarily, U1 can be 4.0V, 4.02V, 4.05V, 4.08V, 4.09V, 4.091V, 4.095V, 4.099V, or a range of any two of the above values. U2 can be 3.40V, 3.42V, 3.45V, 3.48V, 3.49V, 3.50V, 3.51V, 3.52V, 3.53V, 3.55V, 3.58V, 3.60V, or a range of any two of the above values.
[0073] The second type of lithium manganese iron phosphate material, due to the incorporation of manganese, has two voltage platforms: a manganese platform and an iron platform, which is a relatively high voltage platform compared to materials such as lithium iron phosphate. The combined use of the first and second types of lithium manganese iron phosphate materials results in a significant voltage boost in the composite cathode active material, with a voltage approaching the ideal voltage platform of 4.1V for manganese, which can significantly improve the energy density of the composite cathode active material.
[0074] In the embodiments of this application, the discharge voltage plateau has a well-known meaning in the art and can be detected using methods and equipment well-known in the art. For example, a charge-discharge curve is obtained by charging and discharging at a rate of 0.1C, and the discharge curve has a first discharge voltage plateau and a second discharge voltage plateau.
[0075] In some embodiments, the resistivity of the composite positive electrode active material powder is from 1 Ω·cm to 500 Ω·cm. Alternatively, the resistivity of the powder is from 5 Ω·cm to 480 Ω·cm. For example, the resistivity of the composite positive electrode active material powder can be 1 Ω·cm, 5 Ω·cm, 10 Ω·cm, 15 Ω·cm, 16 Ω·cm, 20 Ω·cm, 28 Ω·cm, 30 Ω·cm, 40 Ω·cm, 43 Ω·cm, 50 Ω·cm, 60 Ω·cm, 68 Ω·cm, 80 Ω·cm, 100 Ω·cm, 102 Ω·cm, 120 Ω·cm, 150 Ω·cm, 160 Ω·cm, 180 Ω·cm, 200 Ω·cm, 250 Ω·cm, 280 Ω·cm, 300 Ω·cm, 313 Ω·cm, 320 Ω·cm, 350 Ω·cm, 400 Ω·cm, 450 Ω·cm, 500 Ω·cm, or any range of two of the above values.
[0076] In the embodiments of this application, the resistivity of the composite positive electrode active material powder has a well-known meaning in the art and can be measured using instruments and methods well-known in the art, such as a four-probe instrument.
[0077] In some embodiments, the powder compaction density of the composite positive electrode active material is between 2.19 g / ml and 2.40 g / ml. Exemplarily, the powder compaction density of the composite positive electrode active material can be 2.19 g / ml, 2.20 g / ml, 2.22 g / ml, 2.25 g / ml, 2.30 g / ml, 2.35 g / ml, 2.38 g / ml, 2.40 g / ml, or a range of any two of the above values. A powder compaction density within the above range is beneficial for improving energy density.
[0078] In some embodiments, the X-ray diffraction (XRD) pattern of the first lithium manganese iron phosphate material has characteristic peaks I(020) and I(200), and I(020) / I(200) > 2.1.
[0079] The X-ray diffraction (XRD) pattern of the second type of lithium manganese iron phosphate material has characteristic peaks I(020) and I(200), and I(020) / I(200)≤2.1.
[0080] In some embodiments, the first lithium manganese iron phosphate material has a nanosheet structure, and the thickness of the first lithium manganese iron phosphate material is H, with the unit being nm, and 10 ≤ H ≤ 80. For example, the thickness of the first lithium manganese iron phosphate material can be 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, or any range of two of the above values.
[0081] When the thickness of the first lithium manganese iron phosphate material is within the above range, it is beneficial for the first lithium manganese iron phosphate material to be distributed between the particles of the second lithium manganese iron phosphate material, forming a conductive network structure. This can improve the intrinsic resistance of the composite positive electrode active material and increase the conductivity of the powder.
[0082] In the embodiments of this application, the thickness of the material has a meaning known in the art and can be tested using instruments and methods known in the art; for example, a certain amount of the above-mentioned composite positive electrode active material is taken, and then the material is subjected to transmission electron microscopy (TEM) analysis to obtain a TEM image. Then, the thickness of multiple (e.g., more than 30) particles is measured on the TEM image, and the average value is taken as the average thickness of the material.
[0083] In some embodiments, based on the total mass of the composite cathode active material, the mass percentage of the first lithium manganese iron phosphate material is B1%, the mass percentage of the second lithium manganese iron phosphate material is B2%, and 1 ≤ B2 / B1 ≤ 19. When the mass percentages of the first and second lithium manganese iron phosphate materials meet the above range, the discharge voltage plateau of the composite cathode active material can be significantly improved, thereby increasing the energy density of the battery cell. For example, the mass percentage ratio B2 / B1 of the second lithium manganese iron phosphate material and the first lithium manganese iron phosphate material can be 1, 2, 5, 6, 7, 8, 10, 12, 14, 15, 16, 17, 18, 19, or a range consisting of any two of the above values.
[0084] In some embodiments, 5 ≤ B1 ≤ 50; alternatively, 10 ≤ B1 ≤ 30. Exemplarily, the mass percentage B1% of the first lithium manganese iron phosphate material can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, or a range of any two of the above values.
[0085] In some embodiments, 50 ≤ B2 ≤ 95; alternatively, 70 ≤ B2 ≤ 90. Exemplarily, the mass percentage B2% of the second lithium manganese iron phosphate material can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, or a range of any two of the above values.
[0086] In some embodiments, the volume average particle size of the first lithium manganese iron phosphate material is D. v50-1 Its unit is nm; the volume average particle size of lithium manganese iron phosphate materials is D. v50-2 Its unit is nm; 1≤D v50-2 / D v50-1 ≤16; optionally, 2≤D v50-2 / D v50-1≤16. For example, D v50-2 / D v50-1 It can be 1, 1.2, 1.5, 2.0, 2.5, 3.0, 4.0, 5.0, 6.0, 8.0, 10.0, 11, 12, 15, 16 or a range of any two of the above values.
[0087] The embodiments of this application prepare a composite material by mixing two types of lithium manganese iron phosphate particles with different particle sizes. By improving the packing density between particles through the gradation relationship between particles, the composite material can have a relatively high compaction density and improve the energy density of the battery cell.
[0088] The second type of lithium manganese iron phosphate material consists of spherical and / or near-spherical particles with relatively large particle sizes and pores between particles. The first type of lithium manganese iron phosphate material, with relatively smaller particle sizes, fills the pores of the second type of lithium manganese iron phosphate material. This can be understood as the first type of lithium manganese iron phosphate material being uniformly distributed on the surface of the second type of lithium manganese iron phosphate material. The interconnectedness of the first type of lithium manganese iron phosphate material forms a three-dimensional conductive network structure, reducing the intrinsic resistance of the composite cathode active material and improving the overall ionic and electronic powder conductivity of the composite cathode active material, thereby enhancing the low-temperature performance and rate performance of the battery cell.
[0089] In some implementations, 50≤D v50-1 ≤300. For example, the volume average particle size of the first lithium manganese iron phosphate material can be 50nm, 80nm, 100nm, 150nm, 180nm, 200nm, 250nm, 300nm or any combination of two of the above values.
[0090] In some implementations, 200≤D v50-2 ≤800. For example, the volume average particle size of the second lithium manganese iron phosphate material can be 200nm, 230nm, 250nm, 300nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 800nm or any range of two of the above values.
[0091] In this application, the volume average particle size Dv50 of the material has a well-known meaning in the art, representing the particle size corresponding to a cumulative volume distribution percentage of 50%, which can be tested using instruments and methods known in the art. For example, it can be conveniently tested using a laser particle size analyzer, such as the Mastersizer 2000E laser particle size analyzer from Malvern Instruments Ltd., UK, in accordance with GB / T 19077-2016 Particle Size Distribution Laser Diffraction Method.
[0092] In some embodiments, the specific surface area of the first lithium manganese iron phosphate material is S1, and its unit is m². 2 / g; The specific surface area of lithium iron phosphate second-phosphate materials is S2, and its unit is m. 2 / g; 0.4≤S2 / S1<1.0. For example, S2 / S1 can be 0.4, 0.6, 0.7, 0.8, 0.9 or a range of any two of the above values.
[0093] When the specific surface area of the first lithium manganese iron phosphate material and the specific surface area of the second lithium manganese iron phosphate material are within the above range, it is more conducive to the formation of a connected conductive network structure of the first lithium manganese iron phosphate material, thereby improving the electronic powder conductivity and electronic powder conductivity of the composite positive electrode active material.
[0094] In some embodiments, 20 ≤ S1 ≤ 50. Optionally, 22 ≤ S1 ≤ 35. For example, the specific surface area of the first lithium manganese iron phosphate material can be 20 m². 2 / g、25m 2 / g、30m 2 / g、40m 2 / g, 50m 2 / g or a range consisting of any two of the above values.
[0095] In some implementations, 8 ≤ S2 ≤ 20. For example, the specific surface area of the second manganese iron lithium phosphate material can be 8 m². 2 / g, 10m 2 / g, 15m 2 / g、18m 2 / g、20m 2 / g or a range consisting of any two of the above values.
[0096] In this application, the specific surface area of the material has a meaning known in the art and can be tested using instruments and methods known in the art, such as nitrogen adsorption specific surface area analysis and calculated using the BET (Brunauer Emmett Teller) method. The nitrogen adsorption specific surface area analysis can be performed using a NOVA 2000e specific surface area and pore size analyzer from CANTA Corporation, USA.
[0097] In some embodiments, the first lithium manganese iron phosphate material and the second lithium manganese iron phosphate material each independently comprise a material with the molecular formula LiFe. (1-x) Mn x Compounds of PO4 and their modified compounds, wherein 0.5 ≤ x < 1. In this application, modification refers to doping or coating modification of the material.
[0098] For example, the first lithium manganese iron phosphate material includes LiFe 0.5 Mn 0.5 PO4, LiFe 0.4 Mn 0.6 PO4, LiFe 0.3 Mn 0.7 PO4 and LiFe 0.2 Mn 0.8 One or more of PO4.
[0099] For example, the second lithium manganese iron phosphate material includes LiFe 0.5 Mn 0.5 PO4, LiFe 0.4 Mn 0.6 PO4, LiFe 0.3 Mn 0.7 PO4 and LiFe 0.2 Mn 0.8 One or more of PO4.
[0100] battery cell
[0101] Secondly, this application also provides a battery cell.
[0102] A battery cell, also known as a rechargeable battery or accumulator, is a battery that can be recharged after discharge to activate its active materials and continue to be used. Typically, a battery cell includes an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode, a negative electrode, and a separator. The separator is located between the positive and negative electrodes and mainly serves to prevent short circuits between the positive and negative electrodes, while allowing active ions such as lithium ions to pass through.
[0103] The battery cell of this application includes a positive electrode sheet, which includes a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector. The positive electrode film layer includes the composite positive electrode active material of the first aspect of this application. Therefore, the battery cell of this application can improve energy density.
[0104] [Positive electrode plate]
[0105] In some embodiments, the positive current collector has two surfaces opposite each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive current collector.
[0106] In some embodiments, the positive electrode film layer may optionally include a positive electrode conductive agent. This application does not particularly limit the type of positive electrode conductive agent; as an example, the positive electrode conductive agent includes at least one selected from superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage of the positive electrode conductive agent is ≤5 wt% based on the total weight of the positive electrode film layer.
[0107] In some embodiments, the positive electrode film layer may optionally include a positive electrode binder. This application does not impose particular limitations on the type of positive electrode binder. As an example, the positive electrode binder may include at least one selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resins. In some embodiments, the mass percentage of the positive electrode binder is ≤5 wt% based on the total weight of the positive electrode film layer.
[0108] In some embodiments, the positive current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. As an example, the metal material may include at least one of aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. As an example, the polymer substrate may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0109] The positive electrode film is typically formed by coating a positive electrode slurry onto a positive electrode current collector, followed by drying and cold pressing. The positive electrode slurry is typically formed by dispersing a composite positive electrode active material, an optional conductive agent, an optional binder, and any other components in a solvent and stirring until homogeneous. The solvent can be N-methylpyrrolidone (NMP), but is not limited to this. In some embodiments, a first lithium manganese iron phosphate material and a second lithium manganese iron phosphate material can be pre-mixed in a specific ratio, and then an optional conductive agent, an optional binder, and any other components can be added, dispersed in a solvent, and stirred until homogeneous.
[0110] [Negative electrode plate]
[0111] A single battery cell also includes a negative electrode plate.
[0112] In some embodiments, the negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector and comprising a negative electrode active material. For example, the negative current collector has two surfaces opposite each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative current collector.
[0113] The negative electrode active material may be any negative electrode active material known in the art for use in battery cells. As an example, the negative electrode active material may include, but is not limited to, at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. Silicon-based materials may include at least one of elemental silicon, silicon oxide, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may include at least one of elemental tin, tin oxide, and tin alloys.
[0114] In some embodiments, the negative electrode film layer may optionally include a negative electrode conductive agent. This application does not impose any particular limitation on the type of negative electrode conductive agent; as an example, the negative electrode conductive agent may include at least one selected from superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage of the negative electrode conductive agent is ≤5 wt% based on the total weight of the negative electrode film layer.
[0115] In some embodiments, the negative electrode film layer may optionally include a negative electrode binder. This application does not impose any particular limitation on the type of negative electrode binder. As an example, the negative electrode binder may include at least one of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, waterborne acrylic resins (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS). In some embodiments, the mass percentage of the negative electrode binder is ≤5 wt% based on the total weight of the negative electrode film layer.
[0116] In some embodiments, the negative electrode film may optionally include other additives. As an example, other additives may include thickeners, such as sodium carboxymethyl cellulose (CMC), PTC thermistor materials, etc. In some embodiments, the mass percentage of other additives is ≤2 wt% based on the total weight of the negative electrode film.
[0117] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, copper foil may be used. The composite current collector may include a polymer substrate and a metal material layer formed on at least one surface of the polymer substrate. As an example, the metal material may include at least one of copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. As an example, the polymer substrate may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0118] The negative electrode film is typically formed by coating a negative electrode slurry onto a negative electrode current collector, followed by drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, optional conductive agent, optional binder, and other optional additives in a solvent and stirring until homogeneous. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited to these.
[0119] The negative electrode sheet does not exclude other additional functional layers besides the negative electrode film layer. For example, in some embodiments, the negative electrode sheet of this application further includes a conductive undercoat layer (e.g., composed of a conductive agent and an adhesive) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector. In other embodiments, the negative electrode sheet of this application further includes a protective layer covering the surface of the negative electrode film layer.
[0120] Electrolyte
[0121] A single battery cell also includes an electrolyte.
[0122] During the charging and discharging process of a single battery cell, active ions repeatedly insert and extract between the positive and negative electrode plates, while the electrolyte acts as a conductor for these active ions. This application does not impose any particular restrictions on the type of electrolyte; it can be selected according to actual needs.
[0123] Electrolytes consist of electrolyte salts and solvents. The types of electrolyte salts and solvents are not specifically limited and can be selected according to actual needs.
[0124] As an example, the electrolyte salt may include, but is not limited to, at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate (LiDFOB), lithium dioxalate borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorodioxalate phosphate (LiDFOP), and lithium tetrafluorooxalate phosphate (LiTFOP).
[0125] As an example, the solvent may include, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butyl ester carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE).
[0126] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature performance, and additives that improve battery low-temperature power performance.
[0127] [Isolation membrane]
[0128] The battery cell also includes a separator.
[0129] In some embodiments, the battery cell also includes a separator. This application does not impose any particular limitation on the type of separator; any known porous separator with good chemical and mechanical stability can be selected.
[0130] In some embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0131] In some implementations, the positive electrode, separator, and negative electrode can be fabricated into an electrode assembly using a winding process and / or a stacking process.
[0132] In some embodiments, the battery cell may include an outer packaging. This outer packaging can be used to encapsulate the electrode assembly and electrolyte described above.
[0133] In some embodiments, the outer packaging of the battery cell can be a rigid shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of the battery cell can also be a flexible package, such as a pouch. The material of the flexible package can be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0134] This application does not impose any particular limitation on the shape of the battery cell; it can be cylindrical, square, or any other arbitrary shape. Figure 1 The example shown is a square-structured battery cell 5.
[0135] In some implementations, such as Figure 2 As shown, the outer packaging may include a housing 51 and a cover 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates enclosing a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover 53 is used to cover the opening to close the receiving cavity. The positive electrode, negative electrode, and separator may be formed into an electrode assembly 52 by a winding process and / or a stacking process. The electrode assembly 52 is encapsulated in the receiving cavity. Electrolyte is immersed in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 may be one or more, which can be adjusted according to requirements.
[0136] The method for preparing the battery cell of this application is well known. In some embodiments, a positive electrode, a separator, a negative electrode, and an electrolyte can be assembled to form a battery cell. As an example, the positive electrode, separator, and negative electrode can be formed into an electrode assembly through a winding process and / or a stacking process. The electrode assembly is placed in an outer packaging, dried, and then injected with electrolyte. After vacuum sealing, settling, formation, and shaping processes, a battery cell is obtained.
[0137] In some embodiments of this application, the battery cells according to this application can be assembled into a battery module. The number of battery cells contained in the battery module can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.
[0138] Figure 3 This is a schematic diagram of battery module 4 as an example. Figure 3 As shown, in battery module 4, multiple battery cells 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple battery cells 5 can be fixed in place using fasteners.
[0139] Optionally, the battery module 4 may also include a housing with a receiving space in which multiple battery cells 5 are received.
[0140] In some embodiments, the battery modules described above can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0141] Figure 4 and Figure 5 This is a schematic diagram of battery pack 1 as an example. Figure 4 and Figure 5As shown, the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box includes an upper body 2 and a lower body 3. The upper body 2 covers the lower body 3, forming a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0142] In this application embodiment, the battery may include one or more battery cells. In the case where the battery includes multiple battery cells, the battery may include a battery module or a battery pack.
[0143] Electrical appliances
[0144] This application also provides an electrical device, which includes at least one of the battery cell, battery module, or battery pack described in this application. The battery cell, battery module, or battery pack can be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device can be, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0145] The electrical device can be configured to use individual battery cells, battery modules, or battery packs according to its usage requirements.
[0146] Figure 6 This is a schematic diagram of an example electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the device's requirements for high power and high energy density, a battery pack or battery module can be used.
[0147] Another example of an electrical device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use a single battery cell as their power source.
[0148] Example
[0149] The following embodiments describe the disclosure of this application in more detail. These embodiments are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of the disclosure of this application. Unless otherwise stated, all parts, percentages, and ratios reported in the following embodiments are based on mass, and all reagents used in the embodiments are commercially available or synthesized by conventional methods and can be used directly without further processing, and the instruments used in the embodiments are commercially available.
[0150] Example 1
[0151] Preparation of lithium-ion batteries
[0152] 1. Preparation of positive electrode sheet
[0153] Aluminum foil with a thickness of 12μm was used as the positive electrode current collector.
[0154] The positive electrode active material, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) are mixed in an appropriate amount of solvent NMP at a weight ratio of 97.5:1.4:1.1 to form a uniform positive electrode slurry. The positive electrode slurry is uniformly coated on the surface of the positive electrode current collector aluminum foil, and after drying and cold pressing, the positive electrode sheet is obtained.
[0155] 2. Preparation of negative electrode sheet
[0156] A copper foil with a thickness of 8μm was used as the negative electrode current collector.
[0157] The negative electrode active material graphite, the binder styrene-butadiene rubber (SBR), the thickener sodium carboxymethyl cellulose (CMC-Na), and the conductive agent carbon black (Super P) are mixed thoroughly in an appropriate amount of deionized water at a weight ratio of 96.2:1.8:1.2:0.8 to form a uniform negative electrode slurry. The negative electrode slurry is then uniformly coated onto the surface of the negative electrode current collector copper foil. After drying and cold pressing, the negative electrode sheet is obtained.
[0158] 3. Separating membrane
[0159] Porous polyethylene (PE) membrane is used as the separator.
[0160] 4. Preparation of electrolyte
[0161] In an environment with a water content of less than 10 ppm, non-aqueous organic solvents ethylene carbonate (EC) and diethyl carbonate (DMC) are mixed at a volume ratio of 1:1 to obtain an electrolyte solvent. Subsequently, lithium salt lithium hexafluorophosphate is mixed with the mixed solvent to prepare an electrolyte with a lithium salt concentration of 1 mol / L.
[0162] 5. Preparation of lithium-ion batteries
[0163] The positive electrode, separator, and negative electrode are stacked in sequence, with the separator acting as a separator between the positive and negative electrodes. The electrode assembly is then wound up. The electrode assembly is placed in an outer packaging shell, dried, and then injected with electrolyte. After vacuum sealing, settling, formation, and shaping, a lithium-ion battery is obtained.
[0164] Comparative Example 1
[0165] Comparative Example 1 was prepared using a method similar to that of Example 1, except that the positive electrode active material of Comparative Example 1 was LiFe. 0.4 Mn0.6 PO4 is in the form of spherical particles.
[0166] Comparative Example 2
[0167] Comparative Example 1 was prepared using a method similar to that of Example 1. The difference between Comparative Example 2 and Example 1 is that the positive electrode active material used in Comparative Example 2 is a LiFe nanosphere structure. 0.4 Mn 0.6 PO4 and spherical LiFe 0.4 Mn 0.6 PO4, and A1 = A2, the two materials have different volume average particle sizes.
[0168] Examples 2-1 to 2-4
[0169] Comparative Example 1 was prepared using a method similar to that of Example 1. The difference from Example 1 is that the mass percentage ratio of the first lithium manganese iron phosphate material and the second lithium manganese iron phosphate material was adjusted in Examples 2-1 to 2-4.
[0170] Examples 3-1 to 3-6
[0171] Comparative Example 1 was prepared using a method similar to that of Example 1. The difference from Example 1 is that the volume average particle size ratio of the first lithium manganese iron phosphate material and the second lithium manganese iron phosphate material was adjusted in Examples 3-1 to 3-6.
[0172] Examples 4-1 and 4-2
[0173] Comparative Example 1 was prepared using a method similar to that of Example 1. The difference from Example 1 is that the molecular formulas of the first lithium manganese iron phosphate material and the second lithium manganese iron phosphate material were adjusted in Examples 4-1 and 4-2.
[0174] The data for the examples and comparative examples are shown in Table 1.
[0175] Test section
[0176] 1. Powder compaction density of composite positive electrode active materials
[0177] A certain amount of the above composite positive electrode active material sample was taken and placed in a UTM7305 electronic pressure testing machine with a bottom area of 1.327 cm². 2 In the mold, pressure was applied to 2000 kg (equivalent to 20000 N), held for 30 seconds, then depressurized and held for 10 seconds. The compacted density of the composite positive electrode active material under a force of 20000 N was then recorded and calculated. The test standard was based on GB / T24533-2009.
[0178] 2. Average voltage of individual battery cells
[0179] A coin cell half-cell is formed by combining a positive electrode sheet of unit area with a lithium metal sheet of unit area. The electrolyte composition adopts the electrolyte composition of the example. The cell is fully charged at a rate of 0.1C and then charged and discharged at a rate of 0.1C. The discharge energy density / specific capacity is the average voltage.
[0180] Test Results
[0181] The test results are shown in Table 1.
[0182] Table 1
[0183]
[0184] In Table 1, molecular formula 64 represents LiFe 0.4 Mn 0.6 PO4; molecular formula 73 represents LiFe 0.3 Mn 0.7 PO4; molecular formula 55 represents LiFe 0.5 Mn 0.5 PO4.
[0185] As shown in Table 1, Comparative Example 1 uses spherical lithium manganese iron phosphate material as the positive electrode active material. Compared with Comparative Example 1, Comparative Example 2 adds lithium manganese iron phosphate material with smaller nano-spherical structure, which can improve the average voltage to a certain extent, but the improvement effect is minimal.
[0186] Depend on Figure 7 a to Figure 9 It can be seen that the first lithium manganese iron phosphate material in Example 1 has a sheet-like nanostructure, while the second lithium manganese iron phosphate material has a spherical structure. The composite positive electrode active material formed by mixing the two is a mixture of the two. Figure 10 It can be seen that the discharge platform 1 (corresponding to the first discharge voltage platform) and discharge platform 2 (corresponding to the second discharge voltage platform) in Example 1 have been significantly improved.
[0187] Therefore, it can be seen that by adding lithium manganese iron phosphate material with (010) crystal plane exposed, the capacity of such material is close to the theoretical capacity, which can significantly improve the average discharge voltage of lithium manganese iron phosphate.
[0188] Although this application has been described with reference to preferred embodiments, various modifications can be made thereto and components can be replaced with equivalents without departing from the scope of this application. In particular, the technical features mentioned in the various embodiments can be combined in any manner as long as there is no structural conflict. This application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
Claims
1. A composite positive electrode active material, comprising: The first lithium manganese iron phosphate material has a nanosheet structure, and the (010) crystal surface area of the first lithium manganese iron phosphate material accounts for A1% of the total crystal surface area of the first lithium manganese iron phosphate material; and The second lithium manganese iron phosphate material has a spherical and / or near-spherical structure, and the (010) crystal surface area of the second lithium manganese iron phosphate material accounts for A2% of the total crystal surface area of the second lithium manganese iron phosphate material; the first lithium manganese iron phosphate material and the second lithium manganese iron phosphate material are mixed to obtain a composite positive electrode active material; The composite positive electrode active material satisfies: A1 > A2. The first lithium manganese iron phosphate material is distributed between the particles of the second lithium manganese iron phosphate material. The volume average particle size of the first lithium manganese iron phosphate material is D v50-1 Its unit is nm, 50≤D v50-1 ≤300.
2. The composite positive electrode active material according to claim 1, wherein, The cell parameter b-axis length of the first lithium manganese iron phosphate material is b1, and its unit is nm; The cell parameter b-axis length of the second lithium manganese iron phosphate material is b2, and its unit is nm. Where b1 < b2.
3. The composite positive electrode active material according to claim 2, wherein, b1<100。 4. The composite positive electrode active material according to claim 3, wherein, 10≤b1≤80。 5. The composite positive electrode active material according to claim 2, wherein, b2>100。 6. The composite positive electrode active material according to claim 5, wherein, 200≤b2≤800。 7. The composite positive electrode active material according to claim 1 or 2, wherein, The average voltage of the composite positive electrode active material is 3.55V to 3.81V; and / or The composite positive electrode active material has a first discharge voltage platform U1 and a second discharge voltage platform U2, where 4.0V≤U1<4.1V; and / or 3.4V≤U2≤3.6V.
8. The composite positive electrode active material according to claim 1, wherein, The resistivity of the composite positive electrode active material powder is from 1 Ω·cm to 500 Ω·cm; and / or The compacted density of the composite positive electrode active material is between 2.19 g / ml and 2.40 g / ml.
9. The composite positive electrode active material according to claim 1, wherein, The X-ray diffraction pattern of the first lithium manganese iron phosphate material has characteristic peaks I(020) and I(200), and I(020) / I(200) > 2.1; and / or The X-ray diffraction (XRD) pattern of the second lithium manganese iron phosphate material has characteristic peaks I (020) and I (200), and I (020) / I (200) ≤ 2.
1.
10. The composite positive electrode active material according to claim 1, wherein, The thickness of the first lithium manganese iron phosphate material is H, with units of nm, and 10 ≤ H ≤ 80.
11. The composite positive electrode active material according to claim 1, wherein, Based on the total mass of the composite positive electrode active material, the mass percentage of the first lithium manganese iron phosphate material is B1%, the mass percentage of the second lithium manganese iron phosphate material is B2%, and 1≤B2 / B1≤19.
12. The composite positive electrode active material according to claim 1, wherein, The volume average particle size of the first lithium manganese iron phosphate material is D v50-1 Its unit is nm; The volume average particle size of the second lithium manganese iron phosphate material is D v50-2 Its unit is nm. Where 1≤D v50-2 / D v50-1 ≤16.
13. The composite positive electrode active material according to claim 12, wherein, 2≤D v50-2 / D v50-1 ≤16。 14. The composite positive electrode active material according to claim 12, wherein, 200≤D v50-2 ≤800。 15. The composite positive electrode active material according to claim 1, wherein, The specific surface area of the first lithium iron phosphate material is S1, and its unit is m². 2 / g; The specific surface area of the second lithium iron phosphate material is S2, and its unit is m². 2 / g; Where 0.4 ≤ S2 / S1 < 1.
0.
16. The composite positive electrode active material according to claim 15, wherein, 20≤S1≤50。 17. The composite positive electrode active material according to claim 15, wherein, 8≤S2≤20。 18. The composite positive electrode active material according to claim 1, wherein, The first lithium manganese iron phosphate material and the second lithium manganese iron phosphate material each independently comprise a material with the molecular formula LiFe. (1-x) Mn x Compounds of PO4 and their modified compounds, wherein 0.5 ≤ x < 1.
19. A battery cell comprising a positive electrode sheet, said positive electrode sheet comprising a composite positive electrode active material according to any one of claims 1 to 18.
20. A battery comprising a battery cell as described in claim 19.
21. An electrical device comprising the battery according to claim 20.
Citation Information
Patent Citations
Lithium ion battery anode material manganese lithium phosphate and preparation method thereof
CN101320809A
Preparation method and application of b-axial LiFePO<4> / C nano flake material
CN105244500A
Lithium iron phosphate positive electrode material and preparation method thereof and battery
CN110048109A